The Impact of Mother-Infant Bonding on Periodontal Health Status in the Postpartum Period - Issa, Rula Nabeel; Diab , Ban Sahib (Journal of Baghdad College of Dentistry, 2018)
Background: Mother-infant bonding is an important psychological step postpartum and disturbed relationship may carry dramatic consequences as a psychological disorder which may affect the periodontal health of the mother. The aim of the present study was to assess the effect of the postpartum Mother-infant bonding on their periodontal condition.Materials and Methods: Mothers in the postpartum period with age range 20-35 years were subjected to postpartum Bonding Questionnaire (PBQ). Periodontal health status was assessed by measuring probing pocket depth and clinical attachment level.Results: The mean values of both probing pocket depth (PPD) and clinical attachment loss (CAL) were higher among disordered mothers than mothers with normal bonding relationship. The mean percentage of PPD according to different thresholds of severity and CAL (1-2 mm) was higher among the disordered mothers.Conclusion: Mother-infant bonding disorder could influence the periodontal health status of the mother.